PENGARUH PEMERIKSAAN KEHAMILAN (ANTENATAL CARE) PADA IBU HAMIL TERHADAP LUARAN BAYI BERAT LAHIR RENDAH (BBLR) DI RUMAH BERSALIN DI KOTA MEDAN TAHUN 2010 - Maryani Simanjuntak (Jurnal Ilmiah Kebidanan Imelda, 2015)
There were 301 (0.6%) out of 52.613 newborn babies were BBLRs (low weight newborn babies) in Medan in 2010. Most of the BBLRs were found in four subdistricts: 54 babies (6.9%) at Medan Barat Subdistrict, 76 babies (6.2%) at Medan Helvetia Subdistrict, 55 babies (9.1%) at Medan Deli Subdistrict. and 69 babies (6.7%) at Medan Labuhan Subdistrict. In these four subdistricts, there were 254 BBLRs out of 3,639 newborn babies. The aim of this research was to analyze the influence of Ante Natal Care of pregnant mothers on the birth of low weight newborn babies (BBLR) in the Maternity Clinics in Medan in 2010. The type of the research was an explanatory survey. The population was 254 mothers who had their pregnancy examined and who gave birth to low weight babies recorded in the medical records in the maternity clinics in four subdistricts: Medan Barat Subdistrict, Medan Helvetia Suubdistrict, Medan Deli Subdistrict, and Medan Labuhan Subdistrict in 2010. 100 BBLRs were used as the samples which were taken by using proportional random sampling. The data were collected from the secondary data which were obtained in the medical records. The data were analyzed by using Kruskall Wallis, followed by Mann Whitney at the level of reliability of α = 95%. The results of the research showed that the weight of pregnant mothers, the giving of iron substance (Fe) tablets, the height of fundus uterus. The examination of mothers’ pregnancy and the giving of toxoid immunization to pregnant mothers did not influence the birth of low weight newborn babies. It is recommended that the management of Medan Health Service and authorities concerned should increase the program of pregnancy examination through posyandu (integrated service post) activities and home visits. It is also recommended that the health workers should give health promotion and services, especially in pregnancy examination, according to 7T program. Moreover, pregnant mothers should find health information, have their pregnancy examined regularly, and carry out what the health workers ask them to do in order to prevent the accident of low weight newborn babies.